Conductivity and dielectric analysis of cellulose based solid polymer electrolytes doped with ammonium carbonate (NH4CO3) - M.I.H Sohaimy; Mohd Ikmar Nizam Mohamad Isa (Trans Tech Publications, Switzerland, 2024)
The present work investigated the effect of carboxy methylcellulose (CMC) solid polymer electrolytes doped with ammonium carbonate (AC) prepared from solution cast technique. The CMC-AC solid polymer electrolytes system has been analyzed using EIS to understand its conductivity and dielectric behavior at temperature range of 303 K to 363 K. The highest conductivity achieved at room temperature (303K) is 7.71 x 10-6 S cm-1 doped with 7wt.% of AC and all samples follows Arrhenius behaviour. The dielectric constant (?r) value was found to be dependent of ionic dopant.